Preliminary Evaluation of a Community-Based Parent Mentor Program: Empowering Families to Navigate Special Education - Cornell, Heidi R.; Stone, Jennifer (Journal of the American Academy of Special Education Professionals, 2023)
Parent-to-Parent individualized mentoring is an understudied strategy that has potential for supporting parents of children with disabilities as they learn to navigate the special educational planning process. Preliminary findings from a formative evaluation of individualized, intensive parent-to-parent mentoring services are shared. Data were collected from a pre-post Family Empowerment Scale survey, as well as an open-ended questionnaire for school professionals. While significant increases in parent empowerment were achieved, analysis of data from school professionals uncovered critical questions that are important for the field to explore further.